A Descriptive Study of Long Term Effects of Retained Pellets inside Human Body - Azher Mushtaq; Atif Naeem Raja (Current Innovations in Medicine and Medical Science Vol. 7, 2022)
The study was performed in a tertiary care hospital of Government Medical College Srinagar. It included a cohort of 70 pellet hit individuals all having pellets retained in different parts of the body in varying numbers. The patients were kept in follow up from 2016 to the end of 2017 and later. The patients were monitored for specific symptoms related to pellets, relative position of pellets and need for removal. Pellet trauma is a rare type of weapon violence, and there aren’t many published studies in the literature for the immediate and long-term management of such victims. So there are no clear protocols available. Instead of So here are no clear protocols available. We concluded from our study that patients who have retained pellets inside their body need to be monitored until they are symptom-free, and the pellets need to be removed only if their existence interferes with a person’s everyday activities.